2013
DOI: 10.1097/brs.0000000000000034
|View full text |Cite
|
Sign up to set email alerts
|

Foot Drop Caused by Single-Level Disc Protrusion Between T10 and L1

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…As we have reported previously, foot drop can be caused by a single‐level herniated disc between T 10 and L 1 ; our findings are consistent with those of Tokuhashi et al , who reported three cases of T 12 –L 1 disc protrusion with foot drop . In the present study, all patients with foot drop associated with single‐level hard disc herniation between T 10 and L 1 showed excellent surgical outcomes after decompression, suggesting that this procedure provides satisfactory outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As we have reported previously, foot drop can be caused by a single‐level herniated disc between T 10 and L 1 ; our findings are consistent with those of Tokuhashi et al , who reported three cases of T 12 –L 1 disc protrusion with foot drop . In the present study, all patients with foot drop associated with single‐level hard disc herniation between T 10 and L 1 showed excellent surgical outcomes after decompression, suggesting that this procedure provides satisfactory outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…The weaker strength was used for analysis in patients with bilateral foot drop. Surgical outcomes were classified according to the postoperative muscle strength of the TA as excellent when muscle strength had recovered to grade 4 or 5, good when it had recovered to grade 3, fair when it had improved but remained below 3, and poor when there was no improvement in muscle strength at the final follow‐up . The recovery rate of muscle strength was evaluated as follows: recovery ratio (%) = (grade at final follow‐up) – (grade before operation)/(5 − grade before operation) × 100%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can also suggest that thoracic intervertebral disc herniation may remain a missed diagnosis, if it is not considered within the range of preliminary diagnoses in cases with dorsalgia. [16][17][18][19][20] In conclusion, several conclusions may be made regarding the MRI findings in patients with dorsalgia. Magnetic resonance imaging is a precise imaging technique for investigating patients with complaint of dorsalgia.…”
Section: Discussionmentioning
confidence: 96%
“…Most of the published FD cases due to central etiologies are due to brain lesions, including cerebral infarction, intra-cranial tumor, traumatic brain injury and multiple sclerosis [ 5 , 8 ]. Some articles reported that thoracic spine disc protrusion cases with FD could be due to UMNL [ [14] , [15] , [16] ]. However, our literature review found only one reported case of unilateral central FD was due to cervical pathology [ 3 ] ( Table 1 ), with which we are unable to directly compare our findings precisely.…”
Section: Discussionmentioning
confidence: 99%